The flipped classroom has received a large amount of attention in the educational research literature with its most frequently reported advantage is of the improvement of students’ learning performance. This inverted classroom approach precedes face-to-fa - Harunasari, Siti Yulidhar (International Journal of Psychosocial Rehabilitation, 2020)
The flipped classroom has received a large amount of attention in the educational research literature with its most frequently reported advantage is of the improvement of students’ learning performance. This inverted classroom approach precedes face-to-face classroom lecture by reversing homework elements of a course to self- regulated learning. Students are presented with course material in advance; reading a book chapter or website page, viewing a video, or working with any digital tools. The in-class time then is used for purposes other than the delivery of information. However, whether the students see the flipped format positively; whether the format meets the course aim, and also, what the challenges students encounter in out-of-class activities are, were the rising issues. To answer the questions, the author of this paper used a flipped classroom model to teach English Phonology, a course in the English education undergraduate program with 44 students. One of the key objectives in this course is to enable students to understand the act of producing the English sounds. A case study methodology was applied to investigate the effectiveness of the flipped classroom approach. This study used an anonymous online survey to determine if the model was positive from the students’ point of view and to identify the challenges they faced in out-of-class activities. Students’ grades and the author’s observations are used for examining if the model meets the course aim. The main findings showed that the flipped classroom should alter the traditional model of teaching English Phonology course. Regardless, there were still few students who favored the traditional lecture model instead of the flipped classroom, the majority of students were satisfied with the flipped classroom model, and the positive view was brought forward. To sum, the flipped classroom promoted a higher-level understanding and skill performance on English pronunciation.